SARS-CoV-2 infection establishes a stable and age-independent CD8+ T cell response against a dominant nucleocapsid epitope using restricted T cell receptors - Choy, Cecily; Chen, Joseph; Li, Jiangyuan; Gallagher, D. Travis; Lu, Jian; Wu, Daichao; Zou, Ainslee; Hemani, Humza; Baptiste, Beverly A.; Wichmann, Emily; Yang, Qian; Ciffelo, Jeffrey; et al. (Nature communications, 2023)
The resolution of SARS-CoV-2 replication hinges on cell-mediated immunity, wherein CD8 + T cells play a vital role. Nonetheless, the characterization of the specificity and TCR composition of CD8 + T cells targeting non-spike protein of SARS-CoV-2 before and after infection remains incomplete. Here, we analyzed CD8 + T cells recognizing six epitopes from the SARS-CoV-2 nucleocapsid (N) protein and found that SARS-CoV-2 infection slightly increased the frequencies of N-recognizing CD8 + T cells but significantly enhanced activation-induced proliferation compared to that of the uninfected donors. The frequencies of N-specific CD8 + T cells and their proliferative response to stimulation did not decrease over one year. We identified the N 222-230 peptide (LLLDRLNQL, referred to as LLL thereafter) as a dominant epitope that elicited the greatest proliferative response from both convalescent and uninfected donors. Single-cell sequencing of T cell receptors (TCR) from LLL-specific CD8 + T cells revealed highly restricted Vα gene usage (TRAV12-2) with limited CDR3α motifs, supported by structural characterization of the TCR–LLL–HLA-A2 complex. Lastly, transcriptome analysis of LLL-specific CD8 + T cells from donors who had expansion (expanders) or no expansion (non-expanders) after in vitro stimulation identified increased chromatin modification and innate immune functions of CD8 + T cells in non-expanders. These results suggests that SARS-CoV-2 infection induces LLL-specific CD8 + T cell responses with a restricted TCR repertoire. Although SARS-CoV2 epitope characterization has been the focus of extensive research, these efforts have largely focused on the spike protein. Here, the authors demonstrate that CD8 + T cell responses can be directed against a dominant nucleocapsid epitope and rely on a highly focused T cell receptor repertoire.